(3BOGH GdYQH hGdaQSs - (3CMeO Hf eMeO Hf jYbhH perSncnhrjg, CHh Ydj,J (B421 (3g` s ((3CMeO GdSgQhOi s)
(3ChdgG (B:s
(3ZjQg CPcQ eY cd fYeg RhGdgG heY cd HdjI cTagG aEf Pdc CHbi ddfYeI s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B168s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B21 - (3U (B419 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B43s
Keywords: (3GdCOHs